Evaluation of the Equivalency Education Program at PKBM Insan Mandiri Using the Kirkpatrick Model - Rista Ayudya Hapsari; Yudan Hermawan (Universitas Negeri Padang, 2026)
Equivalency education programs serve as a crucial bridge for individuals marginalized by formal schooling. This study evaluates the equivalency education program at PKBM Insan Mandiri using the Kirkpatrick model (reaction, learning, behavior, and results). Employing a qualitative descriptive approach, data were collected via observation, documentation, and interviews with nine informants (four learners, four tutors, and one PKBM head). Data analysis utilized an interactive model of reduction, display, and conclusion drawing. Findings reveal that at the reaction level, learners express satisfaction with methods and tutor interactions. At the learning level, participants show improved knowledge, skills, and attitudes. At the behavior level, positive changes in discipline, responsibility, and social participation emerge. Finally, at the results level, the program demonstrates positive outcomes in supporting participants’ academic and economic independence. Thus, the program plays a constructive role in human resource development. Recommendations include strengthening digital facilities and continuous tutor training to optimize learning outcomes.